Preparation method and application of PTFE-based manganese-cobalt bimetallic catalytic filter material
Patent Information
- Application Number
- CN202510543555.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-04-28
AI Technical Summary
[0004]本发明的目的在于提供一种具有高的低温脱硝活性,突破催化剂理论活性且催化剂与滤料结合的脱硝除尘一体化催化过滤材料的制备方法及其应用,以解决上述技术背景中提到的现有技术方法催化过滤材料制备方法复杂、低温活性和催化剂理论活性阈值难突破等问题
[0027]1、通过聚多巴胺的表面功能化改性和微波辅助沉积在滤料纤维表面成功负载了锰钴复合金属氧化物脱硝催化剂,同时利用微量硼氢化钠对其进行活化,这样不仅大幅提升了滤料的催化性能,也不会破坏原有滤料的物化性能和结构,保留了其用作袋式除尘器的除尘功能。此外,还通过多巴胺改性了原本惰性的聚合物纤维表面,使催化剂在滤料表面分散均匀,结合牢固。
Smart Images

Figure CN120479485B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalytic filter material technology, specifically relating to a method for preparing and applying a PTFE-based manganese-cobalt bimetallic catalytic filter material. Background Technology
[0002] Smoke and nitrogen oxides (NOx) released during industrial combustion processes x ), sulfur oxides (SO) x Pollutants such as dust and NO are the main causes of smog and acid rain. High-temperature flue gas emission sources, such as coal-fired power plants and new dry-process cement kilns, as well as medium- and low-temperature stationary sources such as waste incinerators and metal smelting kilns, are all major sources of dust and NO emissions. x Co-emissions. Existing treatment systems mostly employ a series process of selective catalytic reduction (SCR) and non-woven fabric baghouse dust collectors. In this process, SCR technology uses a catalyst to remove NO... x The process transforms NH3 into harmless N2. Among numerous technologies, NH3, with its high conversion rate, excellent selectivity, and significant practicality as a reducing agent, has become the mainstream treatment solution. Meanwhile, needle-punched felt filter media, with its three-dimensional network structure, enables baghouse dust collectors to maintain a stable dust content of less than 30 mg / m³ in the flue gas after dust removal. 3 However, split-type purification systems have inherent drawbacks such as large footprint, lengthy process flow, and high equipment investment costs. By developing composite filter media with surface catalytic function, NO can be simultaneously eliminated during dust filtration. x Catalytic conversion can be used to build integrated flue gas purification systems, which simplifies equipment space requirements compared to traditional processes and reduces operating costs, making it of significant engineering application value for promoting in-depth treatment of industrial flue gas.
[0003] Patent application CN202411941141.3 discloses a method for preparing and applying PTFE catalytic filter media. The preparation of PTFE catalytic filter media includes the preparation of MnCeTi catalyst, PTFE catalytic fiber preparation, heteropolyacid functionalization, and needle punching. While heteropolyacid functionalization further optimizes surface oxygen vacancies and acidic sites, improving the low-temperature catalytic performance of the PTFE catalytic filter media, other patents such as CN103191603A, CN112755997A, CN116870586A, and CN114699845A also involve stepwise preparation of highly active low-temperature denitrification catalysts, followed by loading them onto polymer filter media. While these methods can ensure catalytic activity to a certain extent, they also suffer from problems such as complex processes, large catalyst loading, and uneven distribution. Patent application CN202410698133.4 discloses a method for preparing and applying a PPS-supported ternary Mn-based catalyst. The method involves reacting cleaned PPS filter media with trimethylchlorosilane to obtain chloromethylated PPS filter media, followed by reaction with ammonia to introduce amino groups into the PPS filter media. The ternary Mn-based catalyst is then immobilized onto the PPS filter media via an in-situ synthesis method. This in-situ loading method effectively solves the problem of catalyst detachment in traditional methods, but it also causes some damage to the filter media, thus affecting its original filtration performance. Furthermore, conventional low-temperature synthesis methods, lacking a high-temperature activation step, have consistently hampered the development of high-temperature catalytic activity in the filter media. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing an integrated denitrification and dust removal catalytic filter material with high low-temperature denitrification activity, breaking through the theoretical activity of catalysts and combining catalyst with filter media, and its application, so as to solve the problems mentioned in the above-mentioned technical background, such as the complexity of the preparation method of catalytic filter materials, and the difficulty in breaking through the low-temperature activity and theoretical activity threshold of catalysts.
[0005] The objective of this invention can be achieved through the following technical solutions:
[0006] A method for preparing PTFE-based manganese-cobalt bimetallic catalytic filter media involves using PTFE needle-punched filter media as a carrier, uniformly loading a manganese-cobalt composite metal oxide denitration catalyst onto the surface of the filter media fibers through surface functionalization modification with polydopamine and microwave-assisted deposition reaction, and simultaneously activating the catalyst layer with a trace amount of sodium borohydride to obtain the catalytic filter media.
[0007] This method not only breaks through the theoretical threshold of manganese-cobalt catalysts, but also, while maintaining the original physicochemical properties and structural integrity of the filter material, fully preserves the dust removal function of the filter bag, and successfully modifies the surface of the inert polymer fiber with dopamine. The filter material, modified with trace amounts of sodium borohydride after microwave-assisted deposition of the manganese-cobalt composite metal oxide denitration catalyst, exhibits excellent denitration activity under low-temperature conditions. Simultaneously, thanks to the strong binding effect of polydopamine, a stable bonding interface is formed between the catalyst and the filter material matrix.
[0008] Specifically, the above preparation method includes the following steps:
[0009] (1) After immersing the cleaned PTFE filter material in ethanol for a period of time, take it out and let it stand.
[0010] (2) Immerse the filter material in step (1) in an alkaline solution of dopamine and stir it at a certain temperature for a period of time so that the surface of the filter material fiber is uniformly coated with a polymer functional layer.
[0011] (3) After removing the polymer-modified PTFE filter material from the solution, rinse it with deionized water and ethanol and dry it.
[0012] (4) Immerse the dried filter material from step (3) in deionized water, add cobalt salt and potassium permanganate in sequence, stir continuously at room temperature for a period of time, and then let it stand for a period of time.
[0013] (5) Transfer the entire solution containing the filter material from step (4) into a microwave oven and react it for a period of time at a certain power.
[0014] (6) After the solution in step (5) has cooled to room temperature, remove the solution loaded with Mn-CoO. x The modified PTFE filter media of the composite metal oxide catalyst was rinsed with deionized water and ethanol and then activated and dried at a certain temperature.
[0015] (7) Immerse the dried filter material from step (6) in a certain concentration of alkaline sodium borohydride solution and stir it at a certain temperature for a period of time to fully activate the catalyst layer;
[0016] (8) After the activated PTFE filter material is taken out of the solution, it is rinsed with deionized water and ethanol and then vacuum dried at a certain temperature to obtain the catalytic filter material.
[0017] Preferably, the soaking time in step (1) is 0-12h and the standing time is 0-2h.
[0018] Preferably, the concentration of dopamine in step (2) is 0.1-10 g / L, the solvent in the alkaline solution is a mixture of deionized water and ethanol in any proportion, and one or more compounds of sodium hydroxide, potassium hydroxide, ammonia or tris(hydroxymethyl)aminomethane are added to adjust the pH value to between 8 and 10; the stirring temperature is between 0 and 100°C, and the stirring reaction time is 0.5-48 h.
[0019] Preferably, the drying temperature in step (3) is between 50-150°C and the drying time is between 0.5-48h.
[0020] Preferably, the cobalt salt in step (4) is selected from one or more of cobalt chloride, cobalt nitrate, cobalt sulfate, cobalt phosphate and cobalt sulfite; and the mass ratio of filter material to potassium permanganate is controlled between 2:1 and 20:1, and the molar ratio of cobalt salt to potassium permanganate is between 0:1 and 5:1; the stirring reaction time is 0.5-48h; and the standing time is 0.5-48h.
[0021] Preferably, the microwave-assisted deposition reaction power in step (5) is 900W; the microwave reaction time is 0-20min.
[0022] Preferably, the activation and drying temperature in step (6) is between 50-150°C, and the drying time is between 0.5-48h.
[0023] Preferably, in step (7), the concentration of sodium borohydride is 0-0.5 g / L, the solvent in the alkaline solution is a mixture of deionized water and ethanol in any proportion, and one or more compounds of sodium hydroxide, potassium hydroxide, ammonia or tris(hydroxymethyl)aminomethane are added to adjust the pH value to between 9 and 12; the stirring temperature is between 0 and 100°C, and the stirring reaction time is 0-8 h.
[0024] Preferably, the vacuum drying temperature in step (8) is between 50-150°C and the drying time is between 0.5-48h.
[0025] Another object of the present invention is to provide the application of the catalytic filter material prepared by the above method in dust removal and denitrification, especially in industrial flue gas dust removal and denitrification.
[0026] The beneficial effects of this invention are:
[0027] 1. A manganese-cobalt composite metal oxide denitration catalyst was successfully loaded onto the surface of filter media fibers through surface functionalization modification with polydopamine and microwave-assisted deposition. Simultaneously, it was activated using trace amounts of sodium borohydride. This not only significantly improved the catalytic performance of the filter media but also preserved its original physicochemical properties and structure, maintaining its dust removal function as a bag filter. Furthermore, dopamine modification of the originally inert polymer fiber surface ensured uniform dispersion and strong bonding of the catalyst on the filter media surface.
[0028] 2. By precisely controlling the oxygen vacancies on the catalyst surface through trace amounts of sodium borohydride, the surface active sites of the catalyst were effectively activated. The activated manganese-cobalt-based binary metal oxide denitration catalyst has better low-temperature denitration activity, providing a new solution to the limitation of the theoretical activity threshold of low-temperature denitration catalysts.
[0029] 3. The preparation method of the catalytic filter material provided by the present invention has the advantages of being green, simple, and inexpensive, and therefore has broad application prospects in industrial flue gas treatment. Attached Figure Description
[0030] The invention will now be further described with reference to the accompanying drawings.
[0031] Figure 1 This is a diagram of a self-made tubular SCR reactor used in the catalytic filter media activity test.
[0032] Figure 2 Microwave-assisted deposition of Mn-CoO in Example 4 of this invention x SEM image of PTFE filter media after being regulated with trace amounts of sodium borohydride in the form of composite metal oxides.
[0033] In the diagram: 1. Gas source; 2. Pressure reducing valve; 3. Flow meter; 4. Mixer; 5. Air preheater; 6. Heating and catalytic reactor; 7. Test sample; 8. Flue gas analyzer. Detailed Implementation
[0034] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0035] like Figure 1The diagram shows a self-made tubular SCR reactor device used to test the activity of the catalytic filter material in the following embodiment. It includes a gas source 1, a pressure reducing valve 2, and a flow meter 3 connected in sequence. The flow meter 3 is connected to the heating and catalytic reactor 6 through a mixer 4 and an air preheater 5. The heating and catalytic reactor 6 is directly connected to a flue gas analyzer 8, and the test sample 7 is placed inside the heating and catalytic reactor 6.
[0036] Example 1
[0037] Immerse approximately 1.2g of cleaned PTFE filter media in an ethanol solution for 10 minutes, then remove and let stand for 5 minutes. Add a 2g / L dopamine solution and adjust the pH to approximately 9 by adding sodium hydroxide. Stir at room temperature for 24 hours. Remove the filter media, rinse with deionized water and ethanol, and dry at 80℃ for 12 hours. Immerse the dried filter media again in deionized water, then add 0.29g of cobalt chloride and 0.12g of potassium permanganate sequentially. Stir continuously at room temperature for 0.5 hours, then transfer to a microwave oven and heat at a certain temperature. The reaction was carried out in a medium for 6 minutes. After the solution cooled, the filter material was removed, rinsed with deionized water and ethanol, and dried at 80℃ for 12 hours. The dried filter material was then immersed in a 0.25 g / L sodium borohydride solution, and the pH value was adjusted to about 10 with sodium hydroxide. The solution was stirred at room temperature for 2 hours. Finally, the filter material was removed, rinsed with deionized water and ethanol, and placed in an oven for vacuum drying at 80℃ for 12 hours. This yielded a PTFE-based manganese-cobalt bimetallic catalytic filter material with microwave-assisted deposition and micro-level sodium borohydride activation regulation.
[0038] Example 2
[0039] Immerse approximately 1.2g of cleaned PTFE filter media in an ethanol solution for 30 minutes, then remove and let stand for 60 minutes. Add a 2g / L dopamine solution and adjust the pH to approximately 9 by adding tris(hydroxymethyl)aminomethane. Stir at room temperature for 24 hours. Remove the filter media, rinse with deionized water and ethanol, and dry at 80℃ for 12 hours. Immerse the dried filter media again in deionized water, then add 0.29g of cobalt chloride and 0.19g of potassium permanganate sequentially. Stir continuously at room temperature for 0.5 hours, then transfer to a microwave oven. The reaction was carried out at a certain power for 1 minute. After the solution cooled, the filter material was taken out, rinsed with deionized water and ethanol, and dried at 80℃ for 12 hours. The dried filter material was then immersed in a 0.125 g / L sodium borohydride solution, and the pH value was adjusted to about 10 with sodium hydroxide. The solution was stirred at room temperature for 2 hours. Finally, the filter material was taken out, rinsed with deionized water and ethanol, and placed in an oven for vacuum drying at 80℃ for 12 hours. This yielded a PTFE-based manganese-cobalt bimetallic catalytic filter material with microwave-assisted deposition and micro-sized sodium borohydride activation regulation.
[0040] Example 3
[0041] Immerse approximately 1.2g of cleaned PTFE filter media in an ethanol solution for 1 minute, then remove and let stand for 10 minutes. Add a 4g / L dopamine solution and adjust the pH to approximately 9 by adding sodium hydroxide. Stir at room temperature for 18 hours. Remove the filter media, rinse with deionized water and ethanol, and dry at 60℃ for 12 hours. Immerse the dried filter media again in deionized water, adding 0.24g of cobalt chloride and 0.14g of potassium permanganate sequentially. Stir continuously at room temperature for 0.5 hours, then transfer to a microwave oven and heat at a certain temperature. The reaction was carried out in a medium for 3 minutes. After the solution cooled, the filter material was removed, rinsed with deionized water and ethanol, and dried at 80℃ for 12 hours. The dried filter material was then immersed in a 0.25 g / L sodium borohydride solution, and the pH value was adjusted to about 10 with sodium hydroxide. The solution was stirred at room temperature for 2 hours. Finally, the filter material was removed, rinsed with deionized water and ethanol, and placed in an oven for vacuum drying at 80℃ for 12 hours. This yielded a PTFE-based manganese-cobalt bimetallic catalytic filter material with microwave-assisted deposition and micro-level sodium borohydride activation regulation.
[0042] Example 4
[0043] Immerse approximately 1.2g of cleaned PTFE filter media in an ethanol solution for 10 minutes, then remove and let stand for 5 minutes. Add a 2g / L dopamine solution and adjust the pH to approximately 9 by adding tris(hydroxymethyl)aminomethane. Stir at room temperature for 24 hours. Remove the filter media, rinse thoroughly with deionized water and ethanol, and dry at 80℃ for 12 hours. Immerse the dried filter media again in deionized water, then add 0.29g of cobalt chloride and 0.19g of potassium permanganate sequentially. Stir continuously at room temperature for 0.5 hours, then transfer to a microwave oven. The reaction was carried out at a certain power for 3 minutes. After the solution cooled, the filter material was removed, rinsed with deionized water and ethanol, and then dried at 80℃ for 12 hours. The dried filter material was then immersed in a 0.25 g / L sodium borohydride solution, and the pH was adjusted to about 10 with sodium hydroxide and stirred at room temperature for 2 hours. Finally, the filter material was removed, rinsed with deionized water and ethanol, and then placed in an oven for vacuum drying at 80℃ for 12 hours, thus obtaining a PTFE-based manganese-cobalt bimetallic catalytic filter material with microwave-assisted deposition and trace sodium borohydride activation control. Figure 2 The image shown is an SEM image of the catalytic filter media prepared in this embodiment.
[0044] Example 5
[0045] Immerse approximately 1.2g of cleaned PTFE filter media in an ethanol solution for 1 minute, then remove and let stand for 10 minutes. Add a 1g / L dopamine solution and adjust the pH to approximately 9 by adding tris(hydroxymethyl)aminomethane. Stir at room temperature for 24 hours. Remove the filter media, rinse with deionized water and ethanol, and dry at 80℃ for 12 hours. Immerse the dried filter media again in deionized water, then add 0.12g of cobalt chloride and 0.19g of potassium permanganate sequentially. Stir continuously at room temperature for 0.5 hours, then transfer to a microwave oven. The reaction was carried out at a certain power for 3 minutes. After the solution cooled, the filter material was taken out, rinsed with deionized water and ethanol, and dried at 80℃ for 12 hours. The dried filter material was then immersed in a 0.125 g / L sodium borohydride solution, and the pH value was adjusted to about 10 with sodium hydroxide and stirred at room temperature for 2 hours. Finally, the filter material was taken out, rinsed with deionized water and ethanol, and placed in an oven for vacuum drying at 80℃ for 12 hours to obtain a PTFE-based manganese-cobalt bimetallic catalytic filter material with microwave-assisted deposition and micro-sized sodium borohydride activation regulation.
[0046] Example 6
[0047] Immerse approximately 1.2g of cleaned PTFE filter media in an ethanol solution for 10 minutes, then remove and let stand for 5 minutes. Add a 2g / L dopamine solution and adjust the pH to approximately 9 by adding tris(hydroxymethyl)aminomethane. Stir at room temperature for 24 hours. Remove the filter media, rinse with deionized water and ethanol, and dry at 80℃ for 12 hours. Immerse the dried filter media again in deionized water, then add 0.29g of cobalt chloride and 0.19g of potassium permanganate sequentially. Stir continuously at room temperature for 0.5 hours, then transfer to a microwave oven. The reaction was carried out at a certain power for 3 minutes. After the solution cooled, the filter material was taken out, rinsed with deionized water and ethanol, and dried at 80℃ for 12 hours. The dried filter material was then immersed in a 0.5 g / L sodium borohydride solution, and the pH value was adjusted to about 10 with sodium hydroxide. The solution was stirred at room temperature for 2 hours. Finally, the filter material was taken out, rinsed with deionized water and ethanol, and placed in an oven for vacuum drying at 80℃ for 12 hours. This yielded a PTFE-based manganese-cobalt bimetallic catalytic filter material with microwave-assisted deposition and micro-sodium borohydride activation regulation.
[0048] Comparative Example 1
[0049] Approximately 1.2 g of cleaned PTFE filter material was immersed in an ethanol solution for 10 minutes. After removal and standing for 5 minutes, a 2 g / L dopamine solution was added, and the pH was adjusted to approximately 9 by adding tris(hydroxymethyl)aminomethane. The mixture was stirred at room temperature for 24 hours. After removal, the filter material was rinsed with deionized water and ethanol, and then dried at 80°C for 12 hours. The dried filter material was then immersed in deionized water again, and 0.29 g of cobalt chloride and 0.19 g of potassium permanganate were added sequentially. The mixture was stirred continuously at room temperature for 0.5 hours, and then transferred to a microwave oven. The reaction was carried out at a certain power for 3 minutes. After the solution cooled, the filter material was removed, rinsed with deionized water and ethanol, and then dried at 80°C for 12 hours. This yielded microwave-assisted deposited Mn-CoO₂. x PTFE filter media composed of composite metal oxides.
[0050] Comparative Example 2
[0051] Immerse approximately 1.2g of cleaned PTFE filter media in an ethanol solution for 10 minutes, then remove and let stand for 5 minutes. Add 2g / L dopamine solution and adjust the pH to approximately 9 by adding tris(hydroxymethyl)aminomethane. Stir at room temperature for 24 hours. Remove the filter media, rinse with deionized water and ethanol, and dry at 80℃ for 12 hours. Immerse the dried filter media again in deionized water, add 0.19g of potassium permanganate, and stir continuously at room temperature for 0.5 hours. Then transfer to a microwave oven and heat at a certain power. After reacting for 3 minutes and cooling the solution, the filter material was removed, rinsed with deionized water and ethanol, and dried at 80°C for 12 hours. The dried filter material was then immersed in a 0.25 g / L sodium borohydride solution, and the pH was adjusted to about 10 with sodium hydroxide. The solution was stirred at room temperature for 2 hours. Finally, the filter material was removed, rinsed with deionized water and ethanol, and placed in an oven for vacuum drying at 80°C for 12 hours. This yielded a PTFE-based pure manganese oxide catalytic filter material with microwave-assisted deposition and micro-active sodium borohydride.
[0052] Denitrification activity test
[0053] The denitrification activity of the catalytic filter media prepared in the above examples and comparative examples was tested under the following conditions: NO and NH3 volume fractions were both 0.05%, O2 volume fraction was 5%, the remainder was N2, and the gas flow rate was 300 mL·min. -1 After the airflow stabilized for 30 minutes, the concentrations of nitrogen oxides at the inlet and outlet were measured using a German M60x flue gas analyzer to calculate the denitrification rate of the catalytic composite filter media. The test temperatures were 160℃ and 180℃. The test results are shown in the table below:
[0054]
[0055]
[0056] During the implementation of the embodiments, it was found that the main factors affecting the low-temperature denitrification performance of the catalytic filter material of the present invention were the concentration of dopamine solution, the molar ratio of manganese and cobalt metal ions, the microwave time, and the amount of sodium borohydride. With the increase of dopamine concentration, metal ion amount, and microwave time, the catalyst loading gradually increased, with the metal ion ratio having the greatest impact on activity. In addition, the amount of sodium borohydride and the reaction time had a significant impact on the number and morphology of surface active sites on the catalyst, thus affecting its low-temperature denitrification activity. When the sodium borohydride concentration exceeded 0.5 g / L, the activity decreased significantly.
[0057] The above detailed embodiments provide a specific description of the analytical methods involved in this invention. It should be noted that the above description is only intended to help those skilled in the art better understand the methods and ideas of this invention, and is not intended to limit the scope of the invention. Without departing from the principles of this invention, those skilled in the art can make appropriate adjustments or modifications to this invention, and such adjustments and modifications should also fall within the protection scope of this invention.
Claims
1. A method for preparing a PTFE-based manganese-cobalt bimetallic catalytic filter material, characterized in that, Includes the following steps: (1) After immersing the cleaned PTFE filter material in ethanol for a period of time, remove it and let it stand; (2) Immerse the filter material in step (1) in an alkaline solution of dopamine and stir it at a certain temperature for a period of time so that the surface of the filter material fiber is uniformly coated with a polymer functional layer. The concentration of dopamine is 0.1-10 g / L. The solvent in the alkaline solution is a mixture of deionized water and ethanol in any proportion, and one or more compounds of sodium hydroxide, potassium hydroxide, ammonia, or tris(hydroxymethyl)aminomethane are added to adjust the pH value to between 8 and 10. The stirring temperature is between 0 and 100°C, and the stirring reaction time is between 0.5 and 48 h. (3) After removing the polymer-modified PTFE filter material from the solution, rinse it with deionized water and ethanol and dry it. (4) Immerse the dried filter material from step (3) in deionized water, add cobalt salt and potassium permanganate in sequence, stir continuously at room temperature for a period of time, and then let it stand for a period of time. The cobalt salt is selected from one or more of cobalt chloride, cobalt nitrate, cobalt sulfate, cobalt phosphate, and cobalt sulfite; and the mass ratio of filter media to potassium permanganate is controlled between 2:1 and 20:1, and the molar ratio of cobalt salt to potassium permanganate is between 0:1 and 5:1; the stirring reaction time is 0.5-48 h; and the standing time is 0.5-48 h. (5) Transfer the entire solution containing the filter material from step (4) to a microwave oven and react it for a period of time at a certain power. The microwave-assisted deposition reaction power is 900W; the microwave reaction time is 3-20min. (6) After the solution in step (5) has cooled to room temperature, remove the solution loaded with Mn-CoO. x The modified PTFE filter media of the composite metal oxide catalyst was rinsed with deionized water and ethanol and then activated and dried at a certain temperature. The activation and drying temperatures are between 50-150℃, and the drying time is between 0.5-48h. (7) Immerse the dried filter material from step (6) in a certain concentration of alkaline sodium borohydride solution and stir it at a certain temperature for a period of time to fully activate the catalyst layer; The concentration of the sodium borohydride solution is 0.25 g / L. The solvent in the alkaline sodium borohydride solution is a mixture of deionized water and ethanol in any proportion, and one or more compounds selected from sodium hydroxide, potassium hydroxide, ammonia, or tris(hydroxymethyl)aminomethane are added to adjust the pH value to between 9 and 12. The stirring temperature is between 0 and 100°C, and the stirring reaction time is 2 to 8 hours. (8) After the activated PTFE filter material is taken out of the solution, it is rinsed with deionized water and ethanol and then vacuum dried at a certain temperature to obtain the catalytic filter material.
2. The method for preparing a PTFE-based manganese-cobalt bimetallic catalytic filter material according to claim 1, characterized in that, The soaking time in step (1) is 10 min-12 h, and the standing time is 5 min-2 h; the vacuum drying temperature in step (8) is between 50-150℃, and the drying time is 0.5-48 h.
3. The method for preparing a PTFE-based manganese-cobalt bimetallic catalytic filter material according to claim 1, characterized in that, The drying temperature in step (3) is between 50-150℃ and the drying time is 0.5-48h.
4. The application of the catalytic filter material prepared by the preparation method according to any one of claims 1-3 in dust removal and denitrification.
Citation Information
Patent Citations
Catalytic filtration material with denitration and dust removal functions and preparation method of catalytic filtration material
CN103191603A
Mn / Fe-MOF loaded polyphenylene sulfide denitration sulfur-resistant filter material and preparation method thereof
CN112755997A
Preparation method and application of denitration and dust removal integrated filter material
CN114699845A
Dust removal and denitration integrated filter cloth as well as preparation method and application thereof
CN116870586A
Preparation method and application of cof reinforced pps immobilized ternary mn-based catalyst
CN118649704B